Modeling of vulnerability, reliability and risk for route choice in urban freight transport - George Vasconcelos Goes (2015)
The problems of urban mobility are related, among others, the spatial distribution of activities, the significant growth of automobile use, associated with a poor public transport system, and the occurrence of negative impacts caused by load handling activities in densely populated areas. The population concentration in cities gives urban centers the role of consumption nuclei, which must be supplied continuously from streams of very different nature and origin. To estimate the reliability, risk and vulnerability associated with the route chosen from several points of origin and destination can represent change in decision making. As the cost incurred on a route to greater risk, greater variability in travel time, or more vulnerable to incidents exceed the projected cost of a route optimized by time (based on the shortest path), such a decision can be reviewed. The general objective of this study was to represent the generalized cost, incorporating the concept of vulnerability, reliability and risk of urban road network for decision making regarding the choice of route for cargo transportation. Thus, we developed a method for modeling the generalized cost that incorporates the three attributes in different supply scenarios. The experiment showed the existence of trade-off (conflicting choice)between the average time variables trip, reliability / risk and the generalized cost. Only the information of time and cost of travel are not sufficient to meet the conditions of delivery of merchandise. For the driver, holds the knowledge of the reliability or the risk of delivery of the goods can be a strategic pillar cost reduction or the medium and long-term market gains.